(untitled) (Journal of Pharma Insights and Research, 2024)
Dyselectrolytemia represents a significant clinical challenge, particularly in elderly patients with comorbid conditions. We present a case of a 72-year-old male with known normal pressure hydrocephalus (NPH) who presented with acute symptoms of vomiting, persistent hiccups, generalized weakness, urinary incontinence, and myalgia. Laboratory investigations revealed severe hyponatremia (118 mEq/L) and hypokalemia (2.6 mEq/L), along with elevated blood glucose levels (258 mg/dL). The patient had a 10-year history of hypertension and diabetes mellitus, managed with telmisartan, amlodipine, metformin, and glimepiride. Cardiac evaluation through 2D echocardiography showed mild tricuspid regurgitation, left ventricular hypertrophy, and slightly elevated pulmonary artery pressure. Treatment included hypertonic saline, tolvaptan, potassium supplementation, antibiotics, and supportive care. Serial monitoring of electrolyte levels showed gradual improvement, with sodium levels normalizing to 138 mEq/L by day three. The patient’s symptoms resolved significantly, leading to discharge on day four with appropriate follow-up recommendations. This case shows the importance of prompt recognition and appropriate intervention in managing dyselectrolytemia in elderly patients with multiple comorbidities. The successful outcome was achieved through a multidisciplinary approach involving physicians, clinical pharmacists, and nursing staff